Warna Dingin Si Pemberi Nyaman - Purbasari, Mita; Jakti, R.A. Diah Resita I. K. (Bina Nusantara University, 2014)
Color is a form of non-verbal communication. It is not a static energy and its meaning can change from one day to the next with any individual. Human experiences color through vision. Color is not something that is fixed to an object or surface, but an event that is triggered only in the observer. Human’s eyes all work in the same way, what happens after that is another matter. A color and composition in color can mean something quite different to every person who looks at it. Different cultures endow color with different meanings depend on a lot of things. This research is all about Purple, Blue, and Green as an individual color as well as in composition can give different impacts to different audiences depending on their background or contexts. The research method is using literature by collecting data from some resources, observing, and analizing the colors’ meaning and their impacts to audience in Jakarta. The result of research can be used as a basic pattern to create art works based on color perception and culture.